Hydrogen‐Bonded Donor–Acceptor Arrays at the Solution–Graphite Interface. Issue 46 (7th August 2018) - Velpula, Gangamallaiah; Li, Mengmeng; Hu, Yunbin; Zagranyarski, Yulian; Pisula, Wojciech; Müllen, Klaus; Mali, Kunal S.; De Feyter, Steven
Abstract: Controlling the nanoscale morphology of organic thin films represents a critical challenge in the fabrication of organic (opto)electronic devices. The morphology of the (multicomponent) thin films in turn depends on the mutual orientation of the molecular components and their supramolecular packing on the surface. Here, it is shown how the surface co‐assembly of electron‐donating and ‐accepting building blocks can be controlled via (supra)molecular design. Hexa‐ peri ‐hexabenzocoronene (HBC) derivatives with multiple hydrogen‐bonding (H‐bonding) sites were synthesized and their co‐assembly with alkyl‐substituted perylene tetracarboxy diimide (PDI) was studied using scanning tunneling microscopy (STM) at the solution–graphite interface. STM data shows that electron‐rich HBCs co‐assemble laterally with electron deficient PDIs via preprogrammed H‐bonding sites with high fidelity. The surface stoichiometry of the two components could be readily tuned by changing the number of H‐bonding sites on the HBC derivatives via organic synthesis. This model study highlights the utility of (supra)molecular design in co‐assembly of building blocks relevant for organic electronics. Abstract : A D‐A in the life : Self‐assembled monolayers formed by hydrogen‐bonded donor–acceptor complexes are described. The surface co‐assembly of electron‐donating and ‐accepting building blocks can be controlled via (supra)molecular design.